Association Between Smartphone Addiction, Phubbing Behavior, and Communication Skills Among Medical Students - Suhaila Trisha Emira; Ratih Yulistika Utami; Nanda Sari Nuralita; Desi Isnayanti (UMSU, 2026)
Introduction: Individuals addicted to smartphones have been shown to phub people due to fear of missing out, social comparison orientation, and loneliness. The association of phubbing can lead to a stuttering in direct communication due to the habit of indirect communication, namely, using smartphones and the internet. Research objectives: To examine the association between smartphone addiction and phubbing behavior and; the association between phubbing behavior and attitudes toward communication skills among medical students. Method: Correlational analysis with a cross-sectional approach; a sample of 76 students; a systematic selection technique was applied, namely by including all subjects who were present and met the criteria, namely respondents must have an odd NPM, until the required number of samples was met. A Spearman correlation analysis was performed to evaluate the strength and direction of the association among smartphone addiction, phubbing behavior, and attitudes toward communication skills. The independent variable studied was smartphone addiction, while the dependent variables were phubbing behavior and attitudes toward communication skills. This study used the Smartphone Addiction Scale–Short Version (SAS-SV), the General Scale of Phubbing (GSP), and the Communication Skills Attitude Scale (CSAS) as measurement instruments. Result: The bivariate analysis revealed a significant positive correlation between smartphone addiction and phubbing behavior (p 0.001; r=0.529). Crucially, a significant negative correlation was found between phubbing behavior and the CSAS outcome (p 0.001; r=−0.587), indicating that greater phubbing is strongly associated with poorer attitudes toward communication skills. Conclusion: There is an association between smartphone addiction and phubbing behavior with attitudes toward communication skills of medical students.